Comprehensive meta-analytical summary on human papillomavirus association with head and neck cancer - Bychkov, V.A.; Nikitina, E.G.; Ibragimova, M.K.; Kaigorodova, E.V.; Choinzonov, E.L.; Litviakov, N.V. (Experimental Oncology, 2016)
An etiological role of high risk human papillomavirus (HPV) in the development of cervical cancer has been well established. Hence, attention of researchers has been focused on the role of HPV in pathogenesis of other malignancies, such as head and neck cancers. An analysis of epidemiological data on the prevalence of HPV infection among healthy people and patients with precancerous lesions and/or cancer is an important step in understanding the role of HPV in head and neck carcinogenesis. More and more data demonstrate the impact of HPV infection on disease outcome. HPVpositive patients have been shown to have better responses to radiotherapy and better overall and diseasefree survival than HPVnegative patients. This review presents data of the metaanalysis based on a large number of original studies on HPV prevalence in patients with precancerous lesions and in patients with oral, oropharyngeal and laryngeal cancers as well as findings on the impact of HPV infection on survival of these patients.